Elements that characterize the preparation of women Softball players in the defensive area/Elementos que caracterizan la preparación de jugadoras de softball en el área defensiva - Orelvis Pérez Santos; Denis Lara Caveda; Juan Reinaldo Pérez Pardo (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
The planning of training loads is considered among the most important elements when conceiving the training plan. Having a notion of the types of load in competitive activity is a reference point for the selection and distribution of training exercises. In addition, recognizing the relevance that reaches in modern softball the defensive aspect, it was proposed as an objective: to determine the elements that characterize the preparation of softball players in the defensive area for each position. For this, it was necessary to use as main empirical methods the revision of documents, scientific observation and measurement, with the purpose of obtaining the total values of the displacements and defensive actions for each of the athletes, according to their position in the playing field. It is concluded that the softball athletes in the defensive area express a variable effort stipulated by the actions they execute, with a predominance of fast actions. It is possible to define the elements that should characterize the athletes' preparation from the defensive point of view, being organized by groups.